Pengaruh Electronic Word Of Mouth dan Citra Merek Terhadap Minat Beli Konsumen pada Waroeng Steak And Shake Bandar Lampung - Devania Pratiwi; Dorothy R.H. Pandjaitan (CV. Multi Kreasi Media, 2023)
In this modern era, consumer buying interest can be seen from how they respond to a product on social media. The rise in the number of internet users can be used to find out how much interest a consumer has in a product. Several factors that cause consumer buying interest are Electronic Word Of Mouth (E-Wom) and Brand Image. This study aims to determine the effect of Electronic Word Of Mouth (E-Wom) and Brand Image variables on Consumer Purchase Interest. The population in this study are consumers of Waroeng Steak And Shake Bandar Lampung. The sampling technique used in this research is non-probability sampling using purposive sampling method with a total sample of 180 respondents. Methods of data collection using the questionnaire method. Methods of data analysis in this study using multiple linear regression analysis. The results showed that there was a positive and significant relationship between Electronic Word Of Mouth (EWom) and Brand Image variables on Consumer Purchase Interest at Waroeng Steak And Shake Bandar Lampung.